Formulações de fotossensibilizador fenotiazínico contendo etanol ou carreador de oxigênio em diferentes pHs. Efeito antimicrobiano em biofilmes de Pseudomonas aeruginosa - Martins, Maritieli Righi (2014)
Our goal was to optimize the antimicrobial photodynamic effect of methylene blue (MB) by adding ethanol or oxygen carrier in the formulation. Pseudomonas aeruginosa PA01 biofilms were formed on acrylic disks for 5 days. Photoactivated formulations contained MB (250 μM) in: buffered water, 10% ethanol (buffer:ethanol, 90:10), 20% ethanol (buffer:ethanol, 80:20) and emulsion carrier (perfluorodecalin:buffer:triton-X100, 60:35:5). The buffer used was a Tris-HCl solution to a pH of 7.4; and sodium acetate/acetic acid to solutions at pH 5.6. Untreated biofilms and exposed to the buffer, 10% ethanol and 20% without polymerization were evaluated as controls. Production of singlet oxygen was measured by photo-oxidation of 1.3-difenilisobenzofuran (75μM). Data of photo-oxidation and CFU (log10) were evaluated by One-Way ANOVA and post hoc Tukey and Dunnett, respectively. Student t-test assessed differences between the same formulation with different pH. Increased production of singlet oxygen was determined on MB diluted in 10% ethanol and 20% at pH 7.4. However, these formulations showed no statistical difference compared to pH 5.6; or in comparison to the MB diluted in buffer. Average data of CFU log10 for compositions of pH 7.4 containing MB/ethanol 10%, MB/ethanol 20% and MB/carrier were 3.99 ± 1.74; 4.04 ± 1.82; 3.82 ± 1.63, respectively. The average microbial reduction of these formulations were 2.47 (P=0.03); 2.42 (P=0.03); and 2.64 (P=0.02), respectively. The other formulations had no significant antimicrobial effect.